Fluctuation studies on the finite interval matrix representations of operator products and their decompositions - Baykara, N. A.; Gürvit, Ercan; Demiralp, Metin (AIP, 2012)
In this work a study on finite dimensional matrix approximations to products of quantum mechanical operators is conducted. It is emphasized that the matrix representation of the product of two operators is equal to the product of the matrix representation of each of the operators when all the fluctuation terms are ignored. The calculation of the elements of the matrices corresponding to the matrix representation of various operators, based on three terms recursive relation is defined. Finally it is shown that the approximation quality depends on the choice of higher values of n, namely the dimension of Hilbert space.